HIV diagnosed in breastfed children after maternal testing at sibling’s birth - Moreira, Isabela Bernardes; Fernandes, Regina Célia de Souza Campos; Medina-Acosta, Enrique (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Breastfeeding provides numerous benefits for mothers, infants, and society. However, in the context of maternal HIV infection, it is contraindicated due to transmission risk. A critical consideration is the possibility of maternal HIV acquisition during breastfeeding, which poses a significant risk of transmitting the virus to the infant. Objective: To report two cases of pediatric HIV infection acquired through breastfeeding, in which the children were only diagnosed after their younger siblings' HIV testing prompted the maternal diagnosis. Methods: Retrospective review of medical records for both cases and follow-up. Results: Case 1: A three-year-old male, born to a mother who tested negative for HIV during pregnancy and at delivery. He was breastfed for two years and six months. The mother was diagnosed with HIV only two months before the birth of his sibling, which prompted the child's diagnosis. Case 2: An 18-month-old male, born to a mother who tested negative for HIV at delivery and was breastfed throughout this period. His mother’s HIV diagnosis occurred at the time of his sibling’s birth, which led to the child's diagnosis. Conclusion: These cases underscore the critical importance of routine clinical follow-up and repeated HIV testing during the breastfeeding period. Both children would have remained undiagnosed if not for the testing conducted during their siblings' births. Maternal HIV acquisition during breastfeeding must be considered to prevent undiagnosed pediatric infections.